Approaches for designing and delivering solid lipid nanoparticles of distinct antitubercular drugs. Issue 6 (13th April 2023) - Vasam, Mallikarjun; Goulikar, Rama Krishna
Abstract: Tuberculosis (TB) is still the biggest infectious disease among adults globally, which effects the social and biological lives of patients as well as the economic liability of healthcare systems. Current treatment regime has challenges with drug resistant (MDR/XDR) strains and the failure of standard therapeutic interventions against these TB strains. In the recent years, several nanocarrier-based drug delivery systems developed (including lipid-based) with anti-tuberculosis drugs via targeted delivery to improve the therapeutic outcomes. In this review, we attempt to summarize on the composition of the reported solid lipid-based particles (SLNPs), their various production methodologies, and properties of the delivery system, and their influence on cellular and pharmacokinetic aspects are also discussed. Besides, we have highlighted anti-TB drugs delivering via lipid-based systems have shown promising outcomes, however clinical translation of such systems is still under investigation. Based on recent advancements and reports, it is recommended that future efforts be made to accelerate the translational development of lipid-based nanocarriers to improve TB treatment.